In‐Flight Observation of Positron Annihilation by ILDAS. Issue 15 (3rd August 2018) - Kochkin, P.; Sarria, D.; Skeie, C.; van Deursen, A. P. J.; de Boer, A. I.; Bardet, M.; Allasia, C.; Flourens, F.; Østgaard, N.
Abstract: We report a 511‐keV photon flux enhancement that was observed inside a thundercloud and is a result of positron annihilation. The observation was made with the In‐flight Lightning Damage Assessment System (ILDAS) on board of an A340 test aircraft. The aircraft was intentionally flying through a thunderstorm at 12‐km altitude over Northern Australia in January 2016. Two gamma ray detectors showed a significant count rate increase synchronously with fast electromagnetic field variations registered by an on‐board antenna. A sequence of 10 gamma ray enhancements was detected, each lasted for about 1 s. Their spectrum mainly consists of 511‐keV photons and their Compton component. The local electric activity during the emission was identified as a series of static discharges of the aircraft. A full‐scale Geant4 model of the aircraft was created to estimate the emission area. Monte Carlo simulation indicated that the positrons annihilated in direct vicinity or in the aircraft body. Key Points: A sequence of 10 X‐ray pulses was observed from an aircraft inside thundercloud at 12‐km altitude The pulses contain strong enhancement of the positron annihilation line (511 keV) Each pulse lasts for 1 s and is accompanied by a static discharge from the aircraft